Vocal cordopathy consequent to bronchial asthma inhalation therapy - Ahmed Mohammed Abumossalam; Hanan Abdelsattar Ahmed; Omar Mohamed Ibrahim; Talal Mohamad Saad Algreisy; Abdullah Mohmad Al-Shenqiti (The Egyptian Journal of Bronchology, 2020)
Abstract Background Vocal cords signify an imperative lane for air flow in and out of the respiratory tract along with a phonetic role. So, the aim of this work is to assess the impact of habitual versus occasional utilization of inhalation therapy of patients with bronchial asthma on their vocal cords regarding visual endoscopic pathological changes in addition to phonetic dysfunction. This study was conducted on 112 diagnosed bronchial asthma patients (66 male and 46 females). They were classified into the following: group A (habitual user), 65 patients with severe persistent asthma with regular frequent intake of inhalation therapy, and group B (occasional user), 47 patients with intermittent asthma with alternating intake of inhalation therapy. They were submitted to clinical, vocal assessment plus laryngoscopic examination. Results The habitual users group demonstrated that laryngeal edema and hyperemia attained the higher percentage in the adult than children age group (60%, 40–67.3%, 50%) respectively together after 6 and 9 months of study followed by laryngeal nodules (5.4%, 0–9%, 10%). Occasional users presented the same findings comparable to the habitual group (27%, 10–32.4%, 20%). Cord paresis, cord dysfunction, and fungal plaques were in the second frequencies in both age groups with the same percentage (3.6%) at the end of the study; however, in occasional users, fungal plaques illustrated low percentage (2.7%, 5.4–0, 10%, respectively). Conclusion Inhalation therapy as a form of asthma medication correlated with major counter effects on vocal cords with well-recorded laryngeal hyperemia, edema, and vocal nodules in addition to fungal plaques moreover phonetic dysfunction.